THE PROTECTIVE ROLE OF CAMELLIA SINENSIS LEAVES EXTRACT AGAINST HISTOPATHOLOGICAL CHANGES IN SPLEEN OF RATS THAT INDUCED BY DEN AND CCL4 - Hasan, Halah Flaeeih; Mohammed, Jabbar Abadi (PT. Antis International Publisher, 2025)
Objective: The current study was performed in the animal house at the Faculty of Science, University of Kufa, for the period from 2/1/2025 to 2/6/2025. Method: (36) laboratory rats (Rattus rattus) were used. The animals were divided into six groups as follows: The first group(G1): the control group treated only with the feed and water. The second group(G2): The infection group was injected with Diethylnitrosamine (DEN) and given for two weeks, then it was injected with Carbon tetrachloride (CCL4) for six weeks to induce cancer. The third group(G3): treated with alcoholic extract of Camellia sinensis leaves at a concentration of 10 mg/kg for two months. The fourth group(G4): treated with alcoholic extract of C.sinensis leaves at a concentration of 20 mg/kg for two months. The fifth group(G5): treated with alcoholic extract of C.sinensis leaves at a concentration of 10 mg/kg for two weeks, after which the mixture of DEN + CCL4 was given until the end of the experiment. The sixth group(G6): treated with alcoholic extract of C.sinensis leaves at a concentration of 20 mg/kg for two weeks, after which the mixture of DEN + CCL4 was given until the end of the experiment. The treatment continues for two months, after which the animals are dissected, the organs are extracted and preserved in sand for making after completing histological sections, they are studied, the histological changes were read using light microscopy. Results: The histological study in the groups treated with alcoholic extract of C.sinensis leaves showed no histological changes in spleen tissue compared with the second group treated with the substances (DEN and CCL4). The results of the histological study also showed the protective role in the groups were treated with alcoholic extract of C. sinensis leaves were then treated with substances that cause cancer in the spleen, it showed no histological changes or evidence of the presence of cancer cells. Novelty: The results of the current study demonstrate the protective role of alcoholic extract of C. sinensis leaves in preventing histopathological changes in spleen.